Indonesian cultural policy, 1950-2003: culture, institutions, government - Jones, Tod (Curtin University, 2005)
This thesis examines official cultural policy in Indonesia, focussing on the cultural policy of the national governments from 1950 until 2003. Drawing on Michel Foucault’s writings about government and debates about cultural policy in Cultural Studies, the study proposes that the features of cultural policy in Indonesia are primarily determined by the changing ways that the state has put culture to work in its versions of modern governance. Part I of the thesis provides a history of official cultural policy, including a background chapter on the late colonial era and the Japanese occupation. Although contemporary cultural policy was first articulated within Western liberal democracies to shape self-governing national citizens, the Dutch colonial cultural policy differed in that it assumed indigenous subjects had reduced capacities and focussed on managing ethnic populations. The cultural policies of subsequent governments maintained the twin imperatives of ‘improving’ individuals and managing populations, but with different understandings of both imperatives. While a more autonomous subject was assumed during Constitutional Democracy, Guided Democracy exercised greater state guidance as part of Sukarno’s mobilisation of the population behind his political program. Cultural policy during the New Order era rejected Sukarno’s ‘politicisation’ of culture, replaced ‘improvement’ with ‘development’ and further strengthened the role of the state in providing cultural guidance, a move justified by designating Indonesians backward by modern standards.The Japanese administration was the first government to address a national population. Relations among indigenous ethnic populations and between ethnicity and the nation were addressed in cultural policy from 1956 and were central to cultural policy throughout the New Order era. Part II of the thesis consists of two case studies of cultural programs in the New Order and Reform eras: (1) the arts councils and cultural parks and (2) a cultural research project. It explores New Order centralism, demonstrating the heterogeneity between different levels of the state and how governmental goals imbued particular practices and objects with special significance and meaning by constructing them as culture. Cultural policy in the post-Suharto period is addressed in both Parts I and II. While the practices of the New Order era are generally continuing, decentralisation created the possibility of a plurality of cultural policies across Indonesia, as lower levels of government are responsible for administering cultural policy. Decentralisation could result in a more participatory cultural policy as more cultural practices are addressed or a narrowing of cultural policy if conservative ethnic identity politics drives changes.